Validity and reliability of a 6-a-side small-sided game as an indicator of match-related physical performance in elite youth Brazilian soccer players - Aquino, Rodrigo (2019)
The aims of this study were: (i) to compare the external and internal load during a 6-a-side small-sided game (6v6-SSG) according to age-group; (ii) to relate these parameters between the 6v6-SSG and official matches; and (iii) to test the reliability of the 6v6-SSG. A total of 51 Brazilian youth soccer players participated in this study (U11 [n = 16]; U13 [n = 10]; U15 [n = 9]; U17 [n = 8]; U20 [n = 8]). Three experiments were conducted. Experiment A: fifty-one U11 to U20 players were submitted to 6v6-SSGs (n = 10 games; two for each age-group). Experiment B: thirty-two players were randomized to also play official matches (n = 6 matches). Experiment C: thirty-five youth players played the 6v6-SSG twice for test and retest reliability analysis. External load was obtained using Global Positioning Systems and the internal load parameter was calculated through mean heart rate. Statistical approaches showed progressive increases in all parameters according to categories (U11< U13< U15< U17< U20; p < 0.05; ES = 0.4223.68). Even controlling for chronological age, all parameters showed likely to almost certain correlations between 6v6-SSG and official matches (r = 0.250.92). Collectively, the proposed protocol indicates good reliability (CV% = 2.012.6; TE% = 2.32.7%; ICC = 0.780.90). This research suggests that the 6v6-SSG is an alternative tool to indicate match-related physical performance in youth soccer players.